2019
DOI: 10.3390/molecules24030400
|View full text |Cite
|
Sign up to set email alerts
|

Proanthocyanidins Protect against β-Hydroxybutyrate-Induced Oxidative Damage in Bovine Endometrial Cells

Abstract: Metabolic diseases, such as ketosis, are closely associated with decreased reproductive performance (such as delayed estrus and decreased pregnancy rate) in dairy cows. The change of β-hydroxybutyrate (BHBA) concentration in dairy cattle is an important mechanism leading to ketosis, and its blood concentration in ketotic cows is always significantly higher than in nonketotic cows. Many studies indicated that BHBA can induce oxidative damage in liver and other organs. Proanthocyanidins (PCs) have gained substan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 46 publications
4
15
0
Order By: Relevance
“…These results are consistent with a previous study on BHBA in cow primary hepatocytes [35]. Previous studies of our research group also showed that BHBA can cause oxidative stress [36], while this study further confirmed that BHBA can cause changes in cellular oxidation indexes. These findings confirm that PA and BHBA induce oxidative stress in BEND cells in vitro.…”
Section: Discussionsupporting
confidence: 93%
“…These results are consistent with a previous study on BHBA in cow primary hepatocytes [35]. Previous studies of our research group also showed that BHBA can cause oxidative stress [36], while this study further confirmed that BHBA can cause changes in cellular oxidation indexes. These findings confirm that PA and BHBA induce oxidative stress in BEND cells in vitro.…”
Section: Discussionsupporting
confidence: 93%
“…In agreement with our results, the expression of PGR and OXTR among group comparisons has not been found to differ when RGs with different stability are used [13,17]. NRF2 plays an important role in protecting bovine mammary epithelial cells and bovine endometrial cells against oxidative damage [32,33]. However, the relative expression in maternal reproductive tissues and fetal tissues during early pregnancy is unknown.…”
Section: Discussionsupporting
confidence: 89%
“…Ineffective ROS removal results in damage to cellular lipids, proteins and DNA, which in turn impedes the cell signal transduction pathway [27,28]. T-AOC, GSH-Px and T-SOD are a major part of the endogenous anti-oxidant defense system and play a role in maintaining the intracellular redox balance [29][30][31]. MDA levels are a marker of cellular lipid peroxidation, which indirectly reflects the degree of cell damage [32].…”
Section: Discussionmentioning
confidence: 99%